Divergent Roles of Autophagy in Virus Infection - Chiramel, Abhilash; Brady, Nathan; Bartenschlager, Ralf (Cells (Basel, Switzerland), 2013)
Viruses have played an important role in human evolution and have evolved diverse strategies to co-exist with their hosts. As obligate intracellular pathogens, viruses exploit and manipulate different host cell processes, including cellular trafficking, metabolism and immunity-related functions, for their own survival. In this article, we review evidence for how autophagy, a highly conserved cellular degradative pathway, serves either as an antiviral defense mechanism or, alternatively, as a pro-viral process during virus infection. Furthermore, we highlight recent reports concerning the role of selective autophagy in virus infection and how viruses manipulate autophagy to evade lysosomal capture and degradation.